The arabic scene as a foreign language in madaris education in Ibadan metropolis (2020)
This study investigated effective technique of teaching and learning Arabic language in the classroom at selected madaris. The study employed the qualitative method. The participants of the study were three students, three teachers and three parents from three identified Arabic schools in Ibadan. The participants were chosen by purposive sampling procedures. The study revealed that the effective technique of teaching and learning Arabic Language namely contents, the material, method of teaching, the teacher behavior, structure of teaching, learning environment, the students, and time allocated for each subject. As shown in the findings, there was lack of teaching methods which was the main factor of failure in teaching and learning of Arabic Language in Ibadan metropolis. At the same time, the study revealed that applying a good strategy in teaching and smart learning was the key to success in acquiring Arabic Language. A suggested model, namely effective technique for the success of Arabic Language is recommended for the success teaching and learning in Ibadan through the case study of students' teachers and parents in selected madaris in Ibadan.